STRATEGI PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH DI PT. BANK BNI SYARIAH KANTOR CABANG PEMBANTU KOLAKA - Hasriani Zainuddin; Muh Iqbal; Dewi Angraeni (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Bank BNI Syariah Sub-Branch Office Kolaka is one of the financial institutions tasked with raising funds from the public and channeling funds to the public in the form of financing based on sharia principles. Financing at PT. Bank BNI Syariah Sub Branch Office of Kolaka uses murabaha contract, where the financing is inseparable from the constraints that result in problematic financing (default) so a handling strategy is needed in resolving these constraints. The formulation of the problem in this study is what factors cause the occurrence of problematic murabaha financing at PT. BNI Syariah Bank Branch Office Kolaka Assistant? and how the strategies implemented by PT. BNI Syariah Bank Branch Office Kolaka in resolving murabaha financing problems? The research objective is to determine the factors causing the occurrence of problematic murabaha financing and strategies for solving problematic murabaha financing at PT. BNI Syariah Bank Branch Office Kolaka Assistant. The research method used is a qualitative approach to the type of descriptive research. The study was conducted through the stages of observation, interviews and documentation. The results showed that the factors that caused murabaha financing problems at PT. Bank BNI Syariah Sub-Branch Office Kolaka is an external factor (from customers), among others due to a decrease in turnover, customer business closure, demotion, bad character, customers doing dishonest things and deviating from the contract. Therefore, the bank made several efforts to settle this problematic murabaha financing with a collection strategy, deliberation, giving warning letters up to 3 times, rescheduling, taking over, selling other assets, selling voluntary collateral, auctioning, and write off.